Paraneoplastic acute eosinophilic pneumonia due to carotid angiosarcoma: A rare case - Elham Paraandavaji; Homa Hadidi; Mahtab Norouzi; Maryam Azaddehghan; Mohadeseh Khodaparasti; Sasan Shafiei; Erfan Ghadirzadeh; Seyyed Mojtaba Nekooghadam; Hanie Karimi (Clinical Case Reports, 2023)
Key Clinical Message This case report emphasizes that we should analyze a patient's signs and symptoms as a whole rather than relying exclusively on a common pattern to diagnose the condition and indicates that thorough histological investigation and sample collection are needed to accurately diagnose this malignancy. Abstract Angiosarcoma is a rare, fatal, and poorly understood malignant tumor of vascular endothelial cells which is a challenging disease to diagnose in the clinical settings and requires early diagnosis to achieve a favorable prognosis. Paraneoplastic syndromes associated with angiosarcoma can include hypercoagulability, thrombocytopenia, anemia, fever, weight loss, and night sweats. In some cases, the paraneoplastic syndrome can be the first sign of the underlying malignancy. Here, we present a 47‐year‐old individual with angiosarcoma over the right scapula accompanied by hemoptysis and other pulmonary complaints whom at first was thought to be metastatic polmunary involvement. However, the patient's dramatic response to corticosteroids, in addition to further imaging and paraclinical studies, led us to an acute eosinophilic pneumonia (AEP) diagnosis which is an eosinophilic infiltrations of alveolar spaces. The patient received chemotherapy for angiosarcoma and radiation, since the brachial nerve network was disrupted, leaving the tumor unresectable. After 3 years of continuous follow‐up, the patient is now completely cured.